Solar/biomass hybrid cycles with thermal storage and bottoming ORC: System integration and economic analysis - Pantaleo,AM; Camporeale,SM; Sorrentino,A; Miliozzi,A; Shah,N; Markides,CN (Elsevier, 2017)
This paper focuses on the thermodynamic modelling and thermo-economic assessment of a novel arrangement of a combined cycle composed of an externally fired gas turbine (EFGT) and a bottoming organic Rankine cycle (ORC). The main novelty is that the heat of the exhaust gas exiting from the gas turbine is recovered in a thermal energy storage from which heat is extracted to feed a bottoming ORC. The thermal storage can receive heat also from parabolic-trough concentrators (PTCs) with molten salts as heat-transfer fluid (HTF). The presence of the thermal storage between topping and bottoming cycle facilitates a flexible operation of the system, and in particular allows to compensate solar energy input fluctuations, increase capacity factor, increase the dispatchability of the renewable energy generated and potentially operate in load following mode. A thermal energy storage (TES) with two molten salt tanks (one cold and one hot) is chosen since it is able to operate in the temperature range useful to recover heat from the exhaust gas of the EFGT and supply heat to the ORC. The heat of the gas turbine exhaust gas that cannot be recovered in the TES can be delivered to thermal users for cogeneration.The selected bottoming ORC is a superheated recuperative cycle suitable to recover heat in the temperature range of the TES with good cycle efficiency. On the basis of the results of the thermodynamic simulations, upfront and operational costs assessments and subsidized energy framework (feed-in tariffs for renewable electricity), the global energy conversion efficiency and investment profitability are estimated.